Bipartite Promoter Element Required for Auxin Response - Walcher, Cristina L; Nemhauser, Jennifer L (Plant physiology (Bethesda), 2012)
Multiple mechanisms have been described for coordination of responses to the plant hormones auxin and brassinosteroids (Zhang et al., 2009). One unexplained phenomenon is the reliance of the auxin transcriptional response on a functional brassinosteroid pathway. In this study, we used luciferase reporters to interrogate the promoter of SMALL AUXIN-UP RNA15 (SAUR15), a well-characterized auxin and brassinosteroid early response gene in Arabidopsis (Arabidopsis thaliana). After identifying a minimal region sufficient for auxin response, we targeted predicted cis-regulatory elements contained within this sequence and found a critical subset required for hormone response. Specifically, reporter sensitivity to auxin treatment required two elements: a Hormone Up at Dawn (HUD)-type E-box and an AuxRE-related TGTCT element. Reporter response to brassinosteroid treatment relied on the same two elements. Consistent with these findings, the transcription factors BRASSINOSTEROID INSENSITIVE1-EMS SUPPESSOR1 and MONOPTEROS (MP)/ AUXIN RESPONSE FACTOR5 (ARF5) showed enhanced binding to the critical promoter region containing these elements. Treatment with auxin or brassinosteroids could enhance binding of either transcription factor, and brassinosteroid enhancement of MP/ARF5 binding required an intact HUD element. Conservation of clustered HUD elements and AuxRE-related sequences in promoters of putative SAUR15 orthologs in a number of flowering plant species, in combination with evidence for statistically significant clustering of these elements across all Arabidopsis promoters, provided further evidence of the functional importance of coordinated transcription factor binding.